1988
DOI: 10.1210/endo-123-4-1962
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine and Norepinephrine Stimulate the Release of Corticotropin-Releasing Factor-41 from the Rat Hypothalamusin Vitro*

Abstract: The effects of the two putative neurotransmitters acetylcholine and norepinephrine on immunoreactive CRF-41 release from incubated rat hypothalami were studied. Acetylcholine at concentrations of 10(-11) to 10(-7) M stimulated CRF-41 release. This effect was blocked in a dose-dependent manner by the muscarinic antagonist atropine (10(-9) to (-7) M). The nicotinic antagonist hexamethonium was ineffective at a dose of 10(-7) M, but produced slight inhibition of this response at 10(-5) M. Norepinephrine at concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(57 citation statements)
references
References 36 publications
7
49
0
1
Order By: Relevance
“…Intracerebroventricular administration of CRF increases release of NE as measured by microdialysis probes sited in the medial hypothalamus (Lavicky and Dunn, 1993). This stimulatory effect of NE on CRF release has been observed in rat hypothalamic explants and was blocked by beta-adrenergic receptor antagonists, but not alpha adrenergic receptor blocking drugs (Tsagarakis et al, 1988). However, others (Suda et al, 1987) have reported decreased release of hypothalamic CRF after incubation of isolated hypothalamus with nanomolar concentrations of NE that were blocked by both alpha-and beta-adrenergic antagonists.…”
Section: Discussionmentioning
confidence: 90%
“…Intracerebroventricular administration of CRF increases release of NE as measured by microdialysis probes sited in the medial hypothalamus (Lavicky and Dunn, 1993). This stimulatory effect of NE on CRF release has been observed in rat hypothalamic explants and was blocked by beta-adrenergic receptor antagonists, but not alpha adrenergic receptor blocking drugs (Tsagarakis et al, 1988). However, others (Suda et al, 1987) have reported decreased release of hypothalamic CRF after incubation of isolated hypothalamus with nanomolar concentrations of NE that were blocked by both alpha-and beta-adrenergic antagonists.…”
Section: Discussionmentioning
confidence: 90%
“…A recent microdialysis experiment (Tanaka et al, 1991) showed that the temporal profile of norepinephrine release from the amygdala of rats exposed to 20 min restraint stress closely matches that of CRF-IR described in the present work. In vitro norepinephrine evokes CRF-IR release from hypothalamic neurons (Tsagarakis et al, 1988;Hu et al, 1992), while microdialysis experiments show that CRF produces norepinephrine release from nerve terminals in prefrontal cortex and hypothalamus (Lavicky and Dunn, 1993), suggesting the existence of a reciprocal stimulating interaction between CRF and norepinephrine. Although the relevance of central norepinephrine in anxiety is still under debate, some of the behavioral effects produced by stress and ethanol withdrawal involve adrenoreceptor mediation (Berridge and Dunn, 1989;Glue et al, 1989;Soderpalm and Engel, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 4-aminopyridine is known to release norepinephrine and acetylcholine in vitro (Drukarch et al, 1989;Heemskerk et al, 1990). Since norepinephrine or acetylcholine can produce CRF-IR release from the CNS neurons (Tsagarakis et al, 1988;Hu et al, 1992), it cannot be excluded that these or other neurotransmitters mediate the effects of 4-aminopyridine on CRF release within the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…The system has been previously described in detail (16). Male Wistar rats (Banting & Kingham Ltd., Aldbrough, UK), specific pathogen free and weighing 200 to 300 g, were housed four per cage from weaning.…”
Section: Hyporhalumic Expiant Incubationmentioning
confidence: 99%
“…One recent study used a perifusion system of rat hypothalamic fragments to demonstrate a stimulatory role of clonidine on GHRH release (12), but a high concentration of clonidine was required to demonstrate the effect ( W 4 M ) , and no chromatographic characterization of G H R H was obtained. We have previously described a static hypothalamic incubation system for the study of somatostatin (I 3-15), gonadotrophin-releasing hormone (1 5) and corticotrophin-releasing factor-41 release (16), and have now used this system in conjunction with a new RIA for rat GHRH for the investigation of the adrenoceptor control of GHRH.…”
mentioning
confidence: 99%